The EU Falsified Medicines Directive: Key Implications for Dispensers. Issue 1 (2017) - Naughton, Bernard D.
The EU Falsified Medicines Directive (FMD) mandates the serialisation of prescription-only medicines using a two-dimensional (2D) barcode by pharmaceutical companies and the systematic verification of this 2D barcode in pharmacies. This European directive has ramifications for many stakeholders, including market authorization holders, wholesalers, parallel importers, and dispensers. Focusing primarily on the impact on UK dispensers, the following questions are addressed in this article: Where should the affected medicines be scanned? and who will pay for the incoming changes to practice? The role of the EU FMD in terms of drug recalls, the preparation required for EU FMD compliance, and the potential for added healthcare value are also discussed. Dispensers must prepare for the February 2019 EU FMD deadline date by choosing a point within their dispensing processes to scan medicines. Dispensers must also budget appropriately for the incoming costs associated with new hardware and processes.